2021
DOI: 10.5306/wjco.v12.i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary model of brain tumor circulating cells: Cellular galaxy

Abstract: BACKGROUND Although circulating tumor cells (CTCs) have been the focus of consideration for a decade, a categorized cell-based diagnostic strategy is unavailable. The personalized management and complementary/analytical-strategy of data require an alphabetic guide. Therefore, we aimed to determine the behavior of CTCs in tumor and blood in order to provide the hypothetical-based agenda in the brain neoplasms. Exploring the protein expression (PE) using a single cell-based method would clarify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This might be a possible explanation for the difference in methylation changes in tumor tissue and cfDNA. A previous study indicated that a single cell-based method could clarify the heterogeneity and diversity of cancer cells in tumor tissue and blood (CTC) ( 74 ), which might help explore the heterogeneity of tumor tissue in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This might be a possible explanation for the difference in methylation changes in tumor tissue and cfDNA. A previous study indicated that a single cell-based method could clarify the heterogeneity and diversity of cancer cells in tumor tissue and blood (CTC) ( 74 ), which might help explore the heterogeneity of tumor tissue in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The applied processes are performed according to the triangle style, by highlighting the power of cellular network, which reflects the association between the PE of Ets2 is also performed in the peripheral blood of the patients with AD, according to the standard flow cytometry technique[ 11 ]. The PE assay was capable to unveil the nature of heterogeneity/diversity/course of evolution by exploring D1853N polymorphism in ATM gene, and PE assay of vascular endothelial growth factor (VEGF), epidermal growth factor (EGF) at the single cell level of the brain and through the course of evolution[ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another group investigated the role of monocyte chemoattractant protein-1 (MCP-1) in meningiomas and found high expression and a positive correlation between MCP-1 expression and macrophage infiltration ( 88 ). Similarly, CCL2, a monocyte chemoattractant, was found to be highly expressed in meningioma tissue ( 89 ). Cytokine-cytokine receptor interaction networks have already been developed to inform prognostic scoring of meningioma samples ( 72 , 90 ).…”
Section: Immune Signatures Of Meningiomasmentioning
confidence: 99%